Nucleotide sequence that binds primer for DNA synthesis to the avian sarcoma virus genome. - Cordell, B (1976)
Initiation of transcription from the genome of avian sarcoma virus by RNA-directed DNA polymerase in vitro requires tRNAtrp as a primer. The tRNA is bound to the viral genome by a sequence of 16 contiguous nucleotides (U-C-A-C-G-U-C-G-G-G-G-U-C-A-C-Cp), beginning with the penultimate base at the 3' terminus of the primer and extending through the acceptor stem into loop IV of the tRNA. Consequently, the native conformation of the tRNA must be disrupted by the binding of primer to the viral genome. The binding sequence does not include two adjacent residues of pseudouridine in loop IV, which distinguish the primer from many other tRNAs, and the 3' terminal adenosine of primer may also be excluded from base pairing with the viral genome.